Sustainability in the modern architecture of Arica learning from the history - Altikes Pinilla, Pablo (2023)
In this article, some of the most emblematic works of architecture of the modernization of Arica located temporarily between 1958 and 1973 are reviewed based on their energy and environmental behavior, seeking a possible connection with the pre-Columbian cultures that inhabited the desert area.